2013
DOI: 10.1007/s00244-012-9868-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Pollution History on Immunological Responses and Organ Histology in the Marine Mussel Mytilus edulis Exposed to Cadmium

Abstract: The effect of previous toxicant exposure (i.e., exposure history) on an organism's response to re-exposure to the toxicant is of considerable interest. The marine mussel Mytilus edulis was collected from reference and polluted sites in southwest England, and groups of mussels from each site were exposed to 20 μg/L CdCl2 for 0, 1, 4, and 8 days and compared with unexposed controls. End points evaluated were tissue metal and electrolyte concentrations, haemolymph chemistry, haemocyte characteristics [counts, neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…The abundance of MT10‐I and MT10‐II gene transcript was normalized to 18S rRNA gene transcript for each sample. A previous study showed that the expression of 18S gene was a suitable reference gene in mussels and its expressions were stable among different chemical treatments . In this study, expressions of the 18S gene were not significantly different for different control and treatment groups (ANOVA, p > 0.05), and thus this gene was considered as a suitable reference.…”
Section: Methodsmentioning
confidence: 52%
“…The abundance of MT10‐I and MT10‐II gene transcript was normalized to 18S rRNA gene transcript for each sample. A previous study showed that the expression of 18S gene was a suitable reference gene in mussels and its expressions were stable among different chemical treatments . In this study, expressions of the 18S gene were not significantly different for different control and treatment groups (ANOVA, p > 0.05), and thus this gene was considered as a suitable reference.…”
Section: Methodsmentioning
confidence: 52%
“…In bivalves, the digestive gland functions both as a site for metal uptake and as an important reservoir for metal storage; thus, this organ is a main target of metal bioaccumulation (e.g., Sheir et al 2013). Measurements showed significant differences between the two sites and the two times of sampling.…”
Section: Resultsmentioning
confidence: 99%
“…), are in some cases related to the effect of pollutants (De Vico and Carella ), as observed in Mytilus edulis chronically exposed to heavy metals (Sheir et al. ). In this sense, the highest prevalence of hemocytic infiltration in Santa Rosalía clams and the absence of granulocytomas and brown cells in clams from San Lucas beach suggest that these inflammatory responses in Santa Rosalía clams is mainly due to pollution, while hemocytic infiltration in clams from San Lucas beach is likely due to a normal clearance process, reabsorption of residual gametes, and postspawning cellular repair (postspawning stage).…”
Section: Discussionmentioning
confidence: 96%
“…; Sheir et al. ). In Mexico, many coastal ecosystems affected by anthropogenic activities show signs of environmental degradation (García‐Gasca et al.…”
mentioning
confidence: 99%
See 1 more Smart Citation